Comparing Coping Strategies in People Between Inflammatory Bowel Disease and Healthy People in Terms of Health Locus of Control - Sedigheh Bahmani; Adis Kraskian Mujemnari (Gonabad University of Medical Sciences, 2023)
Background: Inflammatory bowel disease (IBD) is a group of disorders that cause chronic inflammation (pain and swelling) in the intestines. IBD includes Crohn disease and ulcerative colitis. Both types affect the digestive system. This study aims to compare coping strategies in people with inflammatory bowel disease and healthy people, according to internal and external sources of health control.  Methods: The present study method was causal-comparative. The study population included all patients with inflammatory bowel disease and healthy people referred to the Bowel Department of the Jam Hospital in Tehran City, Iran, from April to September 2020. The research sample included 200 subjects (87 healthy people and 113 people with inflammatory bowel disease) selected by purposeful sampling. The participants completed the multidimensional health locus of control and the Folkman and Lazarus coping strategies inventory. For the data analysis, statistical indices of mean, standard deviation, distribution indices, and univariate and multivariate analysis of variance were performed in SPSS software, version 24. Results: The findings showed that of 8 coping strategies, two problem-oriented coping strategies, namely positive reappraisal, and responsibility, were seen more in people with IBD, and no difference was seen in other coping strategies between patients and healthy groups (P>0.05). About the variable of the source of health control, it was found that of 8 coping strategies, only the emotion-oriented coping strategy of avoidance was more common in people with an internal locus of control and in using other coping strategies between the two study groups with a source of control no difference was observed between internal and external control. Conclusion: In the present study, according to research, coping strategies are statistically similar in 4 groups of inflammatory bowel disease patients and healthy people.